2021
DOI: 10.1371/journal.pone.0253025
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of diffusion-weighted imaging with background body signal suppression for staging, prognosis, morphology, treatment response, and apparent diffusion coefficient in plasma-cell neoplasms: A single-center, retrospective study

Abstract: Accurate staging and evaluation of therapeutic effects are important in managing plasma-cell neoplasms. Diffusion-weighted imaging with body signal suppression magnetic resonance imaging (DWIBS-MRI) allows for acquisition of whole-body volumetric data without radiation exposure. This study aimed to investigate the usefulness of DWIBS-MRI in plasma-cell neoplasms. We retrospectively analyzed 29 and 8 Japanese patients with multiple myeloma and monoclonal gammopathy of undetermined significance, respectively, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…After induction chemotherapy, the ADC of intra-medullary lesions in MM patients increased significantly except for PD, which was preliminarily confirmed. Yamada et al [ 22 ] found that ADC value of MM treatment responders differed more significantly than that of non-responders (0.154 ± 0.386 × 10 −3 mm 2 /s vs –0.307 ± 0.424 × 10 −3 mm 2 /s, P = .003). In addition, it has been proved that ADC value was negatively correlated with survival time (r = –0.641, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…After induction chemotherapy, the ADC of intra-medullary lesions in MM patients increased significantly except for PD, which was preliminarily confirmed. Yamada et al [ 22 ] found that ADC value of MM treatment responders differed more significantly than that of non-responders (0.154 ± 0.386 × 10 −3 mm 2 /s vs –0.307 ± 0.424 × 10 −3 mm 2 /s, P = .003). In addition, it has been proved that ADC value was negatively correlated with survival time (r = –0.641, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) as part of whole-body magnetic resonance imaging (wb-MRI) is of great clinical value in imaging of MM patients 3,4 and is increasingly recommended for both initial workup and follow-up imaging. [5][6][7][8] Diffusion-weighted imaging allows assessment of the semiquantitative apparent diffusion coefficient (ADC), which has been shown to correlate with histology 9,10 and to differ significantly between the different stages of monoclonal plasma cell disorders, [9][10][11] between different classes of therapy response, 9,[12][13][14][15][16][17][18][19][20][21] and to be of predictive value for progression-free survival and overall survival. 22,23 The texture of the bone marrow is very heterogenous, and there is a large volume of bone marrow in which a region of interest (ROI) can be placed when the ADC is manually measured by radiologists.…”
mentioning
confidence: 99%